Missing link in the Southern Ocean: sampling the marine benthic fauna of remote Bouvet Island - Arntz, Wolf; Thatje, Sven; Linse, Katrin; Avila, Conxita; Ballesteros, Manuel; Barnes, David; Cope, Thérèse; Cristobo, Francisco; Broyer, Claude De; Gutt, Julian; Isla, Enrique; López-González, Pablo; et al. (Polar Biology, 2006)
Bouvet (Bouvetøya) is a geologically young and very remote island just south of the Polar Front. Here we report samples taken during the RV “Polarstern" cruise ANTXXI/2 on 3 days in November 2003 and January 2004. This work was part of SCAR’s EASIZ programme and intended, by providing data on the marine fauna of this “white gap" in the Atlantic sector of the Southern Ocean, to contribute to identifying the role of Bouvet in the faunal exchange between the Sub- and high Antarctic. While this goal demands extensive molecular analysis of the material sampled (future work), a checklist of the samples and data at hand widens the faunal and environmental inventory substantially. We suggest some preliminary conclusions on the relationship of Bouvet Island’s fauna with that of other regions, such as Magellanic South America, the Antarctic Peninsula, and the high Antarctic Weddell Sea, which have been sampled previously. There seem to be different connections for individual higher taxa rather than a generally valid consistent picture.